Identification of sphingosine 1-phosphate level and MAPK/ERK signaling in pancreatic β cells - Ji Hyun Park; Kwan Kyu Park; Jae Young Choe; Kyung Mi Jang (Korean Society of Pediatric Endocrinology, 2021)
Purpose Sphingosine kinase is a lipid kinase that phosphorylates sphingosine to generate sphingosine 1-phosphate (S1P). S1P regulates pancreatic islet β-cell endoplasmic reticulum stress and proliferation. Type 1 and type 2 diabetes share some key pathogenic processes. In this study, we investigated whether secretion of insulin and production of S1P is altered in alloxan and glucose-treated cells from the rat pancreatic β-cell line RIN-5F. Methods RIN-5F cells were treated with 2 mM alloxan and 20 mM glucose for 6 hours or 24 hours before being evaluated by enzyme linked immunosorbent assay (ELISA) and Western blotting. Results Insulin secretion and expression was higher in RIN-5F cells treated with glucose compared to control cells. In contrast, alloxan treatment did not affect insulin secretion and expression in RIN-5F cells. Interestingly, compared with normal control levels, S1P/EDG-5 was increased in both alloxan and glucose-treated pancreatic β cell than normal control. Mitogen-activated protein kinase/extracellular signal-regulated kinase (MAPK/ERK) inhibition strongly decreased the expression of insulin and S1P in glucose- or alloxan-treated RIN-5F cells. Conclusions We observe that production of S1P is increased in both diabetic cell models. In addition, MAPK/ERK signaling regulates secretion of insulin and S1P expression in pancreatic β-cells. Based on the literature and our findings, S1P may be a promising agent for the treatment of insulin-related disorders.